3D numerical investigation on laminar forced convection and heat transfer in a circular tube inserted with right triangular wavy surfaces - Jedsadaratanachai, Withada; Boonloi, Amnart (My University, 2017)
Numerical investigations on flow and heat transfer characteristics in a circular tube heat exchanger inserted with right triangular wavy surfaces are reported. The configurations of the wavy surfaces; incline and V-shape, are studied with flow attack angles of 30°, 45° and 60° for the Reynolds numbers, Re = 100-2000. The numerical results are compared with the smooth circular tube. The mechanisms on flow and heat transfer in the tube heat exchanger with the wavy surface are presented. As the results, the wavy surface can generate the vortex flow and impinging flow through the test section that helps to improve the heat transfer rate and thermal performance. The impingement of the flow on the tube wall disturbs the thermal boundary layer that is an important factor to enhance the heat transfer rate. The V-Downstream wavy surface can create the highest strength of the impinging flow that leads to the highest heat transfer rate. In the range investigate, the augmentations are around 1.2-7.6 and 4-43.6 times above the smooth tube for the heat transfer and friction loss, respectively. In addition, the optimum thermal enhancement factor, TEF, is around 2.42 for the V-Downstream wavy surface at α = 30° and Re = 2000.
Keywords: Flow structure; Heat exchanger; Heat transfer; Right triangular wavy surface; Thermal performance